A Numerical Model Study of the Effect of Interface Shape on Particle Pushing - Agaliotis, Eliana Mabel (2012)
A numerical model using an axisymmetric approximation is developed to study particle pushing during solidification. The model is applied to determine the effect of different parameters on the predicted critical velocity for engulfment of the particle by the solidifying interface. The main parameters considered are particle radius, interface velocity and interface shape as obtained for different thermal conductivities between matrix and particle. The relative thermal conductivity is very important in the pushing/capture process in increasing or decreasing the critical velocity for pushing one order of magnitude, with respect to the critical velocity for a flat interface, depending on whether the interface is concave or convex. Moreover, the predicted critical velocities cover the span of measured values in agreement with the tendency given by the thermal conductivities and particle radius.